Boards of Directors and Corporate Financial Performance: A Review and Integrative Model - Zahra, Shaker A.; Pearce, John A. (Journal of Management, 1989)
This article synthesizes empirical researchfindings on the impact of boards of directors on corporate financial performance. An integrative model of board attributes and roles is presented, and research support on their links is discussed. The review identifies critical short-comings of past studies and concludes by offering an agenda for future studies in this promising area of empirical research.